2021
DOI: 10.21154/elbarka.v4i2.3309
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intellectual Capital Disclosure and Profitability on Value Company

Abstract: The Company's value reflects the assets owned by the company. This study aims to examine the effect of intellectual capital disclosure and profitability on firm value. The Population are manufacturing companies listed on the Indonesia Stock Exchange in 2016 – 2020. The samples of this study are forty-four companies listed in Indonesia Stock Exchange (IDX) selected by using purposive sampling method. The data analysis method used is multiple regression model. Based on the hypothesis tasted proves that the intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
2
0
0
1
Order By: Relevance
“…The policy also disrupts factory activities and limits the ability of suppliers to deliver supplies promptly. In line with the results of previous research, Putri & Rahyuda (2020) and Putra and Marlina (2021) found that profitability has a positive and significant effect on firm value.…”
Section: Profitability Effect Against Firm Valuesupporting
confidence: 91%
See 1 more Smart Citation
“…The policy also disrupts factory activities and limits the ability of suppliers to deliver supplies promptly. In line with the results of previous research, Putri & Rahyuda (2020) and Putra and Marlina (2021) found that profitability has a positive and significant effect on firm value.…”
Section: Profitability Effect Against Firm Valuesupporting
confidence: 91%
“…Good human resource management can create added value for the company. The increase in intellectual capital is an attraction for investors toward company shares, in line with the results of previous research by Putra and Marlina (2021) and Robiyanto et al (2021), who found that intellectual capital has a positive and significant effect on firm value.…”
Section: The Effect Of Intellectual Capital On Firm Valuesupporting
confidence: 90%
“…Pada saat adanya keraguan dalam aktivitas perusahaan, maka dalam penyusunan laporan keuangan sebuah perusahaan dapat menerapkan konservatisme akuntansi (El-Haq et al, 2019). Menurut Noviyanti & Agustina, (2021), (Savitri, 2018), (Rivandi et al, 2017) , (G. H. Putra & Marlina, 2021), (Satria & Fernanda, 2022) Konservatisme secara mudah bisa diinterpretasikan sebagai kehati-hatian (prudent) menggunakan prinsip kehati-hatian sehingga suatu kecenderungan yang terdapat didalam laporan merupakan pesimisme. Akuntansi tidak lagi mengatakan secara pass true value tapi cenderung menetapkan angka laporan yang lebih rendah dari true valuenya.…”
unclassified